Identification of key pathways and genes that regulate cashmere development in cashmere goats mediated by exogenous melatonin - Liu, Zhihong; Liu, Zhichen; Mu, Qing; Zhao, Meng; Cai, Ting; Xie, Yuchun; Zhao, Cun; Qin, Qing; Zhang, Chongyan; Xu, Xiaolong; Lan, Mingxi; Zhang, Yanjun; et al. (Frontiers in Veterinary Science, 2022)
The growth of secondary hair follicles in cashmere goats follows a seasonal cycle. Melatonin can regulate the cycle of cashmere growth. In this study, melatonin was implanted into live cashmere goats. After skin samples were collected, transcriptome sequencing and histological section observation were performed, and weighted gene co-expression network analysis (WGCNA) was used to identify key genes and establish an interaction network. A total of 14 co-expression modules were defined by WGCNA, and combined with previous analysis results, it was found that the blue module was related to the cycle of cashmere growth after melatonin implantation. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the first initiation of exogenous melatonin-mediated cashmere development was related mainly to the signaling pathway regulating stem cell pluripotency and to the Hippo, TGF-beta and MAPK signaling pathways. Via combined differential gene expression analyses, 6 hub genes were identified: PDGFRA, WNT5A, PPP2R1A, BMPR2, BMPR1A and SMAD1. This study provides a foundation for further research on the mechanism by which melatonin regulates cashmere growth.